Subjective Well-being and Peaceful Uprisings - Caroline T. Witte; Martijn J. Burger; Elena Ianchovichina (Tinbergen Institute, 2018)
This study analyzes whether subjective well-being measures can explain variation in peaceful uprisings, in addition to the objective measures typically used in analyses of uprisings. Using a database combining data on uprisings and subjective well-being for 118 countries over the period 2007 to 2014, we find evidence of a positive effect of life dissatisfaction on the incidence of peaceful uprising, but not its violent counterpart. This effect does not depend on the type of political regime, nor the stage of development and reflects, to a large extent, changes to perceived satisfaction with living standards and the ability to have a purposeful and meaningful life.
Keywords: D74; I31; 330; Civil Resistance; Civil Uprisings; Subjective Well-being; Happiness; Political Economy; Grievances; Political conflict